2022
DOI: 10.1111/jfbc.14108
|View full text |Cite
|
Sign up to set email alerts
|

Cordycerebroside A inhibits ICAM‐1‐dependent M1 monocyte adhesion to osteoarthritis synovial fibroblasts

Abstract: Kun-Tsan Lee and Chin-Horng Su contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 55 publications
0
30
0
Order By: Relevance
“…Elevated levels of proinflammatory cytokine expression are found in OA joints [35]. The ACLT animal model for surgical initiation of OA erodes the knee joint cartilage, leading to OA-like disease [6,23]. Here, we found that H. erinaceus mycelium antagonized ACLT-induced promotion of weight-bearing asymmetry, bone loss, synovial inflamma-…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Elevated levels of proinflammatory cytokine expression are found in OA joints [35]. The ACLT animal model for surgical initiation of OA erodes the knee joint cartilage, leading to OA-like disease [6,23]. Here, we found that H. erinaceus mycelium antagonized ACLT-induced promotion of weight-bearing asymmetry, bone loss, synovial inflamma-…”
Section: Discussionmentioning
confidence: 68%
“…Male Sprague-Dawley (SD) rats (eight weeks of age; 300-350 g) were purchased from the National Laboratory Animal Center (Taipei, Taiwan) and randomly divided into three groups: sham surgery (controls), ACLT only and ACLT with H. erinaceus (100 mg/kg). ACLT surgery was performed according to the procedure mentioned in our previous reports [6,23]. Briefly, the rats were anesthetized and underwent arthrotomy to expose the right knee joint, and the ACL was severed.…”
Section: Anterior Cruciate Ligament Transection (Aclt) Animal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Human synovial tissues were stained with anti-CD11b or VCAM-1 antibody and quantified according to the protocol described in our previous work [ 48 , 49 ]. The sum of the intensity and percentage scores was used as the final staining score [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…Allelic discrimination of the SNPs followed previously described assessment procedures 20 - 22 . RNA isolation and RT-qPCR assays followed our previously described procedures 23 - 25 .…”
Section: Methodsmentioning
confidence: 99%